Strategic utopianism and the avoidance of dualisms: An interview with Martin Parker. (Journal of Applied Learning and Teaching, 2021)
Martin Parker is a Professor of Organisation Studies at the School of Management, University of Bristol, the lead for the Bristol Inclusive Economy Initiative and a Distinguished Fellow of the Schumacher Institute. He made headlines with his call and his book to Shut down the business school (2018). Parker’s prolific writings attempt to widen the scope of business and management studies, whether in terms of particular sorts of organisations (the worker co-op, circus, zoo etc.), or ways of representing organising (in art, cartoons, films etc). His recent writing has been about ‘alternative’ organisations (including a book on outlaws). His most recent books are titled Life after Covid-19 and Anarchism, organization and management. In this wide-ranging interview, much of Martin Parker’s fascinating oeuvre is discussed, including the afore-mentioned books and so much more: Parker’s work in the Bristol Inclusion Economy Initiative, the dual character of the hidden curriculum in business schools, the incomplete decolonialisation of curricula, and important influences from Daniel Defoe to David Graeber. Despite the horrific pandemic and the impending climate crisis, Parker promotes anti-binary thinking and strategic utopianism.